Broad-range survey of vector-borne pathogens and tick host identification of Ixodes ricinus from Southern Czech Republic - Honig, Vaclav; Carolan, Heather E; Vavruskova, Zuzana; Massire, Christian; Mosel, Michael R; Crowder, Christopher D; Rounds, Megan A; Ecker, David J; Ruzek, Daniel; Grubhoffer, Libor; Luft, Benjamin J; Eshoo, Mark W (FEMS microbiology ecology, 2017)
Ixodes ricinus ticks are vectors of numerous human and animal pathogens. They are host generalists able to feed on more than 300 vertebrate species. The prevalence of tick-borne pathogens is influenced by host-vector-pathogen interactions that results in spatial distribution of infection risk. Broad-range polymerase chain reaction electrospray ionization mass spectrometry (PCR/ESI-MS) was used to analyze 435 I. ricinus nymphs from four localities in the south of the Czech Republic for the species identification of tick-borne pathogens. Borrelia burgdorferi sensu lato spirochetes were the most common pathogen detected in the ticks; 21% of ticks were positive for a single genospecies and 2% were co-infected with two genospecies. Other tick-borne pathogens detected included Rickettsia helvetica (3.9%), R. monacensis (0.2%), Anaplasma phagocytophilum (2.8%), Babesia venatorum (0.9%), and Ba. microti (0.5%). The vertebrate host of the ticks was determined using PCR followed by reverse line blot hybridization from the tick's blood-meal remnants. The host was identified for 61% of ticks. DNA of two hosts was detected in 16% of samples with successful host identification. The majority of ticks had fed on artiodactyls (50.7%) followed by rodents (28.6%) and birds (7.8%). Other host species were wild boar, deer, squirrels, field mice and voles.
Keywords: host; lidé; Borrelia; Birds; průzkumy a dotazníky; ptáci; Deer; Arvicolinae; klíště; Surveys and Questionnaires; myši; Humans; Borrelia burgdorferi; Mice; Česká republika; Ixodes; vysoká zvěř; Sciuridae; Anaplasma; zvířata; Czech Republic; Lyme borreliosis; Anaplasma phagocytophilum; Tick Infestations; Babesia; Animals; Ixodes ricinus; PCR-ESI/MS; Sus scrofa; tick; Artiodactyla; infestace klíšťaty; Rickettsia